(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Ala household bleach primarily contains sodium hypochlorite as the active ingredient. Sodium hypochlorite (NaOCl) is used for its disinfectant and antiseptic properties. However, exposure to it, either intentionally or accidental, is associated with significant risks due to its strong oxidizing properties. Potentially dangerous scenarios, including ingestion, inhalation, or injection, can lead to considerable morbidity and even mortality. While small accidental ingestions are unlikely to cause clinically significant toxicity, large ingestions may cause corrosive gastrointestinal injury and systemic effects, including metabolic acidosis, hypernatremia, and hyperchloremia. We report here a case of a 26-year-old man who intentionally had taken Ala (bleach) of 150 ml and succumbed to death six hours later. This case highlights the toxicity of bleach with its typical gross and